The effect of energy director on ultrasonic consolidation of multilayered composites (laminates) made from unidirectional PEEK/CF prepregs (Fracture and Structural Integrity, 2025)
The study aims at assessing the effects of the ultrasonic consolidation parameters and the insertion of energy directors from the commercially available polyetheretherketone film ~250 µm thick on the structure and mechanical properties of the layered composites (laminates). Commercially available polyetheretherketone-based prepregs reinforced with tapes of unidirectional carbon fibers were ultrasonically consolidated with and without energy directors from neat polyetheretherketone film using an ‘UZPS-7’ ultrasonic welding machine. The laminates without the energy directors consisted of 16 prepreg layers, while 7 and 6 layers of the prepregs and the energy directors, respectively, included the other ones to ensure similar thicknesses during subsequent interlaminar shear strength tests. In the laminates with the energy directors, prolonging the ultrasonic duration allowed for the prepreg interfaces to be virtually blurred, increasing the interlaminar shear strength value up to the maximum level of 60 MPa. With the energy directors, excessive melting and spreading of the polymer occurred at the prolonged ultrasonic durations, increasing the number of discontinuities at the layer interfaces, including delamination and the impregnation of the prepregs with the excessive binder. The ultrasonic duration of 800 ms was the most rational, as it enabled to reduce the damaging effect of applied ultrasonic vibrations on the joined layers (prepregs), increasing the interlaminar shear strength value above 50 MPa.
Keywords: Laminated composites; PEEK/CF prepregs; ultrasonic consolidation; interlaminar shear strength; interface; discontinuity